Lithology and conditions for formation of the lower-medium-jurassic deposits of the South-Eastern part of the Western-Siberian plate in connection with their oil and gas efficiency; Проблемы геологии и освоения недр; Т. 2 - Zaripova A. D. (Геология, горное и нефтегазовое дело (доклады на английском и немецком языках), 2018)
Заглавие с экрана